Micro-craters in muddy tidal flats of cold regions - Dionne, Jean-Claude (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1972)
Meltwaters dripping from overhanging ice cakes, stranded at low tide on muddy tidal flats of the St.Lawrence Estuary, near Québec City, cause micro-craters to form on soft mud and silty-sand sediments. The shallow depressions are circular, symmetrical, and with rims a few mm high, some have a tiny hole centered in the bottom. Craters range from 7 to 15 cm in diameter, and 20 to 50 mm in depth ; they characterize tidal flats of cold regions.